KONSTRUKSI MAKNA BUDAYA ISLAM PADA MASYARAKAT ACEH - Rasyidah, Rasyidah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Purwokerto, 2012)
This paper explores the culture of Islam that is practiced in ruralcommunities in Aceh. Cultural practices are carried from generation togeneration. This paper uses Berger viewpoint associated with externalizing,internalizing, and objectification that is synergistic with the HerbertBlumer’s theory of symbolic interactionist to see the reality of meaning.The results shows that the cultural practice is still running strong todaydue to the construction of the three pillars of an active role in this community,namely 1) the construction process through intergenerationalvalue transfer, 2) meunasah or mosque as a center for media uniformity ofmeaning that construct and maintain a common meaning, and 3) socialfeedback as the binding effect of community participation.